Targeting Ferroptosis: Effects and Mechanisms of Action of Berberine. - Cheng, Ting; Xi, Hu; Hao, Wenjie; Yang, Yue; Qian, Nannan; Yang, Wenming (American Journal of Chinese Medicine, 2026)
Ferroptosis, a form of regulated cell death characterized by iron-dependent lipid peroxidation, plays a critical role in various diseases. Berberine, a bioactive compound from plants such as Coptis chinensis, tree turmeric, and barberry, exhibits bidirectional regulation of ferroptosis, but its systemic mechanisms remain unclear. This review summarizes berberine's effects through multiple signaling pathways, emphasizing context-dependent mechanisms, tissue-specific accumulation, and therapeutic potential. Relevant literature was retrieved from PubMed, Web of Science, CNKI, and ScienceDirect. Berberine modulates ferroptosis via iron homeostasis, lipid peroxidation, the System Xc−/GSH/GPX4 anti-oxidant system, and mitochondrial function, involving NRF2, p53, AMPK, PI3K/Akt, and MAPK pathways. It promotes ferroptosis in tumors and fibrotic diseases but inhibits it in cardiovascular, metabolic, and neurological disorders, alleviating tissue damage. Nano-delivery systems and structural optimization enhance bioavailability and targeting, demonstrating therapeutic efficacy and biosafety. Berberine's multi-target, bidirectional regulation shows promising clinical potential, warranting further mechanistic and delivery-focused studies.